Process for manufacture of aromatic polymers and polymers manufactured according to process
By providing electrochemical potential between the anode region and the cathode region, and using electron catalytic cathode reaction of aromatic precursors, the problems caused by anodizing and metal catalysts in the prior art are solved, and high-quality production under mild conditions are achieved. The aromatic polymer film ensures the purity and continuity of the film.
Patent Information
- Application Number
- CN202410801264.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-20
- Filing Date
- 2024-06-20
- Publication Date
- 2024-12-20
AI Technical Summary
The existing electrochemical methods rely on anodizing and metal/organometal catalysts when making polymers, which can easily lead to excessive oxidation and poor site selectivity, and insufficient research on cathode coupling reactions, making it difficult to achieve high-quality polymer film manufacturing, especially It is under mild and free of metal catalysts.
Electrochemical methods are used to provide electrochemical potential between the anode region and the cathode region, so that the aromatic precursor can form a polymer through the cathode reaction, and use electrons as catalysts to avoid the use of metal catalysts, and control the polymer film by adjusting the reaction conditions. Size and shape.
It realizes the production of high-quality aromatic polymer films under mild conditions, avoids contamination and deposition of metal catalysts, ensures the purity and continuity of the film, and is suitable for the preparation of large-area and multi-layer polymer films.
Smart Images

Figure CN119162585A_ABST
Abstract
Description
Technical Field
[0001] The present invention generally relates to methods for making aromatic polymers. In particular, the present invention relates to electrochemical methods for making aromatic polymers from aromatic hydrocarbon precursors. The present invention also relates to polymers formed according to the methods. Background Art
[0002] Polymer compounds have a wide range of industrial uses, for example in optoelectronic applications, due to their desirable physical and chemical properties, especially their conjugated species. Polymers are formed by bonding monomers as basic units, usually via carbon-carbon (CC) coupling reactions during polymerization.
[0003] Conventional synthesis methods such as the Ullmann reaction and the Suzuki reaction have been used to produce polymers. However, these methods generally require high pressure, high temperature or metal / organometallic catalysts, which means high costs in terms of materials and production equipment.
[0004] Electrochemical methods are used for polymer compound manufacturing due to their proven properties such as relatively easy setup, environmental friendliness and controllability. However, most existing electrochemical methods rely on anodic oxidation and / or metal / organometallic catalysts to form polymers. Such anodic polymerization is usually prone to over-oxidation and has poor site selectivity. On the other hand, cathodic coupling reactions have been rarely studied, and existing studies are either unrelated to polymers or still involve metal / organometallic catalysts. The use of metal / organometallic catalysts may form unwanted deposits on the electrode surface.
[0005] Therefore, direct fabrication of high-quality polymer films remains a challenge. There is still a need to develop and implement universal cathodic polymerization to allow the preparation of large-area and / or multilayer polymer films in a controllable manner under mild and metal-catalyst-free conditions. Summary of the invention
[0006] One aspect of the present invention relates to a method for producing an aromatic polymer, the method comprising the steps of: providing an anode region and a cathode region; providing an aromatic hydrocarbon precursor; providing an electrochemical potential between the anode region and the cathode region; reacting the aromatic hydrocarbon precursor via the electrochemical potential to form a polymer, the method further comprising the step of performing a cathode reaction.
[0007] Another aspect of the present invention relates to aromatic polymers prepared according to the process of the present invention.
[0008] Without intending to be bound by theory, it is believed that the present invention can provide a novel process for making aromatic polymers, the polymers prepared by the method do not contain other impurities. In addition, the method can control the size (such as thickness) or shape of the polymer film and produce a continuous and smooth surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 An embodiment of the present invention is illustrated, wherein the cyclic voltammogram of 1,4-diiodobenzene in acetonitrile (MeCN) solution containing 0.1 M tetrabutylammonium hexafluorophosphate (TBAPF6) is shown, with a scan rate of 50 mV / s and a starting potential of -1.92 V;
[0010] Figure 2a A slice of one embodiment of the present invention prepared as a poly(p-phenylene) PPP(I) film is illustrated;
[0011] Figure 2b An embodiment of the present invention is illustrated, wherein a PPP(I) film is immersed in different organic solvents under white light;
[0012] Figure 2c An embodiment of the PPP(I) film of the present invention immersed in different organic solvents under 365 nm light is illustrated, from left to right, tetrahydrofuran (THF), toluene, dimethylformamide (DMF), acetone, and chloroform;
[0013] Figure 2d An embodiment of the PPP(I) film of the present invention immersed in different organic solvents under 365 nm light after 4 months is shown, from left to right: THF, toluene, DMF, acetone and chloroform;
[0014] Figure 3a shows a scanning electron microscope (SEM) image of one embodiment of a cross section of the PPP (I) film of the present invention as prepared with a reaction time of 1 hour;
[0015] Figure 3b Another SEM image of one embodiment of a cross-section of the PPP(I) film of the present invention as prepared with a reaction time of 1.5 hours is illustrated;
[0016] Figure 3c Another SEM image of one embodiment of a cross section of the PPP(I) film of the present invention as prepared with a reaction time of 3 hours is shown;
[0017] Figure 3d Another SEM image of one embodiment of a cross-section of the PPP(I) film of the present invention as prepared with a reaction time of 5 hours is illustrated;
[0018] Figure 3e Another SEM image of one embodiment of a cross-section of the PPP(I) film of the present invention as prepared with a reaction time of 12 hours is shown;
[0019] Figure 3fGraph showing the linear relationship between thickness and reaction time of one embodiment of the PPP(I) film thus prepared according to the present invention;
[0020] Figure 4a An embodiment of the PPP(I) film of the present invention formed on an Au electrode having a diameter of 3 mm is illustrated;
[0021] Figure 4b An embodiment of the PPP(I) film of the present invention formed on a Si substrate is illustrated;
[0022] Figure 4c An embodiment of the PPP(I) film of the present invention formed on another Si substrate of different size is illustrated;
[0023] Figure 4d An embodiment of the PPP(I) membrane of the present invention formed on stainless steel is illustrated;
[0024] Figure 4e FTIR spectra of some embodiments of PPP(I) films of the present invention made with different cathode substrates (i.e., Pt, Au, Ni, stainless steel from top to bottom) are illustrated;
[0025] Figure 5a An embodiment of the FTIR spectrum of the thus prepared PPP(I) film and its corresponding 1,4-diiodobenzene precursor of the present invention is shown;
[0026] Figure 5b Graph showing the Raman spectrum of one embodiment of the PPP(I) film thus prepared according to the present invention;
[0027] Figure 5c A photograph of one embodiment of the thus prepared PPP(I) film of the present invention (left) and the corresponding Raman mapping of the area enclosed by the yellow dashed line (right) are illustrated;
[0028] Figure 5d The UV-Vis absorption spectrum (red, i.e., left figure) and fluorescence spectrum (blue, i.e., right figure) of one embodiment of the PPP (I) film thus prepared according to the present invention are shown (λ ex =350nm); the inset shows photographs of some embodiments of the PPP (I) film patterns thus prepared according to the present invention under white light and 365nm light;
[0029] Figure 6a An SEM image of one embodiment of a top view of a PPP (I) film of the present invention after 5 hours of polymerization and corresponding mapping images of elements C (middle) and Si (right);
[0030] Figure 6bA cross-sectional view of one embodiment of the PPP (I) film of the present invention after 12 hours of polymerization and corresponding mapping images of elements C (middle) and Si (right) are shown;
[0031] Figure 7a The figure shows an atomic force microscopy (AFM) height image of one embodiment of the PPP (I) film of the present invention after 5 hours of reaction;
[0032] Figure 7b The diagram shows the Figure 7a The white dashed line in the roughness graph;
[0033] Figure 7c Picture shows Figure 7a 3D image of PPP(I) film in;
[0034] Figure 8a The cyclic voltammogram of one embodiment of 1,4-dibromobenzene in a MeCN solution containing 0.1 M TBAPF6 is shown;
[0035] Figure 8b FTIR spectrum showing one embodiment of the thus prepared PPP(Br) film of the present invention and its corresponding 1,4-dibromobenzene precursor;
[0036] Figure 8c Graph showing the Raman spectrum of one embodiment of the PPP(Br) film thus prepared according to the present invention;
[0037] Figure 9a Graph showing a cyclic voltammogram of one embodiment of 1,4-dibromonaphthalene in a MeCN solution containing 0.1M TBAPF6 at a scan rate of 50 mV / s;
[0038] Figure 9b Graphing the FTIR spectrum of one embodiment of the thus prepared 1,4-polynaphthalene (1,4-PN) film of the present invention and its corresponding 1,4-dibromonaphthalene precursor;
[0039] Fig.9c FIGURES show the fluorescence spectrum of one embodiment of the 1,4-PN thin film thus prepared according to the present invention;
[0040] Fig.10a 1. An SEM image of one embodiment of the 1,4-PN thin film thus prepared herein is illustrated;
[0041] Fig.10b An AMF image of the surface of one embodiment of the thus prepared 1,4-PN thin film of the present invention is shown;
[0042] Fig.10c The diagram shows the Fig.10a The white dashed line in the roughness graph;
[0043] Fig.11a The cyclic voltammogram of one embodiment of 1,5-dibromonaphthalene of the present invention in a MeCN solution containing 0.1M TBAPF6 at a scan rate of 50 mV / s is shown;
[0044] Fig.11b The FTIR spectrum of one embodiment of the 1,5-PN thin film prepared as described above according to the present invention (left figure) and the 1100-400 cm-1 region indicated by the dashed line are shown. -1 Enlarged spectrum within the range (right);
[0045] Fig.12a Graph showing a cyclic voltammogram of one embodiment of 9,10-dibromoanthracene (9,10-DBA) of the present invention in a MeCN / toluene (v / v 8:2) solution containing 0.1 M TBAPF6 at a scan rate of 50 mV / s;
[0046] Figure 12b The FTIR spectrum of one embodiment of the 9,10-PA film prepared as described above and the 1000-400 cm-1 region indicated by the dashed line are shown. -1 Amplified spectrum within the range;
[0047] Fig.13a The cyclic voltammogram of one embodiment of 2,6-dibromoanthracene (2,6-DBA) of the present invention in a MeCN / toluene (v / v 8:2) solution containing 0.1M TBAPF6 at a scan rate of 50 mV / s is shown;
[0048] Fig.13b The FTIR spectrum of one embodiment of the 2,6-PA film prepared as described above according to the present invention (left figure) and the 1000-400 cm-1 region outlined by the dashed line are shown. -1 Amplified spectrum within the range;
[0049] Fig.14a Graph showing a cyclic voltammogram of an embodiment of 2,7-dibromophenanthrene of the present invention in a MeCN / toluene (v / v 8:2) solution containing 0.1 M TBAPF6 at a scan rate of 50 mV / s;
[0050] Fig.14b The FTIR spectra of one embodiment of the as-prepared 2,7-PPA film and its corresponding 2,7-dibromophenanthrene precursor of the present invention are shown.
[0051] Fig.15aGraph showing a cyclic voltammogram of one embodiment of 2,7-dibromopyrene of the present invention in MeCN / toluene (v / v 8:2) containing 0.1 M TBAPF6 at a scan rate of 50 mV / s;
[0052] Fig.15b The FTIR spectrum of one embodiment of the 2,7-PPy thin film prepared as described above according to the present invention (left figure) and the 1150-450 cm-1 region indicated by the dashed line are shown. -1 Enlarged spectrum within the range (right);
[0053] Fig.16a The cyclic voltammogram of one embodiment of 1,3,5-tribromobenzene (TBB) of the present invention in a DMSO solution containing 0.1M TBAPF6 and 3 equivalents of N,N-diisopropylethylamine (DIPEA) at a scan rate of 50 mV / s is shown;
[0054] Fig.16b Graph showing the FTIR spectrum of one embodiment of the poly-TBB (PTBB) film thus prepared according to the present invention;
[0055] Fig.16c Graph showing the Raman spectrum of one embodiment of the PTBB film and its corresponding TBB monomer prepared in the present invention;
[0056] Fig.16d FIG. 1 shows the fluorescence spectrum of one embodiment of the PTBB thin film thus prepared according to the present invention;
[0057] Fig.17a Graph showing a cyclic voltammogram of one embodiment of the present invention of 1,3,5-tris(4-bromophenyl)benzene (TBPB) in a DMSO solution containing 0.1 M TBAPF6 and 3 equivalents of DIPEA at a scan rate of 50 mV / s;
[0058] Fig.17b Graphing the FTIR spectrum of one embodiment of the thus prepared poly-TBPB (PTBPB) film of the present invention;
[0059] Fig.17c Graphs show the Raman spectra of one embodiment of the PTBPB film and its corresponding TBPB monomer prepared as described above according to the present invention;
[0060] Fig.17d FIGURES show the fluorescence spectrum of one embodiment of the PTBPB thin film thus prepared according to the present invention;
[0061] Fig.18a A simplified scheme of one embodiment of the electrochemical dehalogenation of the present invention is illustrated;
[0062] Fig.18b Graph showing the UV-Vis absorption curve of one embodiment of PPP(Br) of the present invention, wherein the photograph inset corresponds to the film thus prepared taken under white light and 365 nm light;
[0063] Fig.18c Graphs showing UV-Vis absorption curves of one embodiment of 1,4-PN of the present invention, wherein the photograph inset corresponds to the film so prepared taken under white light and 365 nm light;
[0064] Fig.18d Graphs showing UV-Vis absorption curves of one embodiment of 1,5-PN of the present invention, wherein the photographic inset corresponds to the film so prepared taken under white light and 365 nm light;
[0065] Fig.18e Graphs showing the UV-Vis absorption curves of one embodiment of the 9,10-PA of the present invention, wherein the photographic inset corresponds to the film thus prepared taken under white light and 365 nm light;
[0066] Fig.18f Graphs showing the UV-Vis absorption curve of one embodiment of 2,6-PA of the present invention, wherein the photograph inset corresponds to the film thus prepared taken under white light and 365 nm light;
[0067] Figure 18g Graphs showing UV-Vis absorption curves of one embodiment of 2,7-PPA of the present invention, wherein the photograph inset corresponds to the film so prepared taken under white light and 365 nm light;
[0068] Figure 18h FIGURES show a UV-Vis absorption curve of one embodiment of 2,7-PPy of the present invention, wherein the photograph inset corresponds to the film thus prepared taken under white light and 365 nm light;
[0069] Fig.18i Graphs showing UV-Vis absorption curves of one embodiment of a PTBB of the present invention, wherein the photographic inset corresponds to the film so prepared taken under white light and 365 nm light;
[0070] Fig.18j Graphs showing UV-Vis absorption curves of one embodiment of PTBPB of the present invention, wherein the photographic inset corresponds to the film so prepared taken under white light and 365 nm light;
[0071] Fig.19 A possible mechanism of one embodiment of the polymerization via electrochemical dehalogenation of the present invention is illustrated;
[0072] Fig. 20 A schematic diagram of a proposed strategy according to one embodiment of the present invention is illustrated, wherein the polymer so prepared can be deposited on the surface of a cathode to produce a smooth film.
[0073] Fig.21a illustrates a schematic diagram of one embodiment of an electrochemical cell of the present invention;
[0074] Figure 21b The diagram shows a Fig.21a Schematic cross-sectional view of an electrochemical cell. DETAILED DESCRIPTION
[0075] Unless expressly stated otherwise, all tests herein were conducted under standard conditions, which included room and test temperatures of 25°C, sea level (1 atm.) pressure, pH 7, and all measurements are in metric units. In addition, all percentages, ratios, etc. herein are by weight unless expressly indicated otherwise. It is to be understood that, unless expressly stated otherwise, the material compounds, chemicals, etc. described herein are generally commercial and / or industrial standards that can be obtained from many suppliers around the world.
[0076] The following preparations and examples are given to enable those skilled in the art to more clearly understand and implement the present invention. They should not be considered as limiting the scope of the present invention, but are merely illustrative, representing some preferred embodiments of the present invention.
[0077] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs.
[0078] As used herein, "aromatic hydrocarbon" refers to an aromatic hydrocarbon containing one or more benzene rings. It includes monocyclic aromatic hydrocarbons (MAH) and polycyclic aromatic hydrocarbons (PAH). It includes unsubstituted aromatic hydrocarbons and aromatic hydrocarbons in which one or more hydrogens on the benzene ring are replaced by, for example, other compounds, functional groups or elements.
[0079] As used herein, "comprising" means including the elements thereafter but not excluding other elements. "Consisting of" means that the material consists of only the corresponding elements, ie, is formed of the corresponding elements.
[0080] As used herein, "catalyst" refers to a material or compound that can initiate a chemical reaction or increase the rate of a chemical reaction in its presence. In the context of this article, electrons can be understood as catalysts in some cases. For example, in some redox reactions or free radical reactions, catalytic cycles can be initiated by electrons. When exogenous electrons enter the cycle to catalyze the reaction, the electrons can leave at the end of the cycle, or the electrons can continue to participate in another cycle. It is obvious to those skilled in the art that the electrons described in the different steps of the catalytic cycle are not necessarily the same electrons, but are intended to emphasize the electron transfer process occurring in the reaction or reaction chain. In some other cases, electrons only act as carriers rather than catalysts in certain reactions, such as in the presence of other catalysts (such as transition metals or organometallics) and electrons only act as carriers in the reaction, and some embodiments of the present invention no longer use catalysts other than electrons to initiate the polymerization of precursors to form polymers.
[0081] As used herein, "cathode reaction" means a reduction reaction that accepts one or more electrons supplied by a cathode. In a typical setup of electrolysis or electropolymerization, the cathode reaction occurs at the cathode or in the cathode region.
[0082] As used herein, "mild and neutral conditions" refers to moderate conditions for the reaction, which are in contrast to those conditions that are considered more violent, such as high temperature and high pressure. In particular, the term herein refers to one or more reaction conditions selected from the group consisting of room temperature or a temperature of about 0°C to about 60°C, atmospheric pressure, no additives, no metal catalysts, neutral pH (i.e., non-acidic or alkaline), and combinations thereof.
[0083] As used herein, "precursor" refers to a compound or material (or group of compounds or materials) that participates in a chemical reaction to produce one or more other compounds. In the case of forming a polymer, a precursor may be a monomer that forms the basic structural unit of the polymer.
[0084] One aspect of the present invention relates to a method for making an aromatic polymer, the method comprising the steps of: providing an anode region and a cathode region; providing an aromatic hydrocarbon precursor; providing an electrochemical potential between the anode region and the cathode region; reacting the aromatic hydrocarbon precursor via the electrochemical potential to form the polymer. The reacting step further comprises performing a cathode reaction.
[0085] Without intending to be limited by theory, it is believed that the electrochemical reduction method herein can overcome one or more of the problems mentioned above due to the fact that electrons are always accumulated at the cathode. It is believed that this can protect the electrodes, especially those made of active metals. In addition, it is believed that by adjusting the reaction conditions, the process herein can directly produce high-quality polyaromatic films on substrates.
[0086] In one embodiment of the present invention, the cathode reaction may include the step of performing a dehalogenation coupling reaction of an aromatic hydrocarbon precursor to form a polymer.
[0087] In some embodiments of the present invention, in the reaction, particularly in the cathode reaction, the electrons can be used as a catalyst for reacting the aromatic precursor to form a polymer. In this way, the reaction utilizes electrons as a catalyst, and no longer uses another catalyst that may have certain disadvantages. For example, some conventional methods using metal or organometallic catalysts may be expensive, causing pollution or inducing deposition on the surface of the electrode. In the reaction, the electrons can be directly used as a catalyst to induce a coupling reaction. In other words, the electrons are used as the main or only catalyst for catalyzing the coupling reaction during the polymerization process.
[0088] In one embodiment of the present invention, the method comprises the steps of providing an anode electrode at the anode region, a cathode electrode at the cathode region; and a solution containing an electrolyte. The anode electrode and the cathode electrode are at least partially in contact with the solution.
[0089] In one embodiment of the invention, the polymer is a conjugated polymer. Polymerization by electrochemical dehalogenation results in an extended π conjugated chain. For example, the polymer can be in the form of a film. In some cases, the polymer can be an unsubstituted conjugated polymer. The unsubstituted conjugated polymer film obtained in this way has relatively good continuity and a smooth surface. The polymer can be a homocyclic aromatic polymer. In some other cases, the polymer can be a heterocyclic polymer.
[0090] In one embodiment of the present invention, the polymer is in a form selected from the group consisting of a dimeric form, an oligomeric form, a polymeric form and combinations thereof.
[0091] Suitable precursors (e.g., aromatic hydrocarbons) can be used in the methods described by these embodiments of the present invention to produce polymers with desired properties. In some cases, one or more hydrogens on aromatic hydrocarbons can be replaced by other functional substituent groups. When some functional substituent groups can promote the quality of the reaction or final product of polymer manufacturing, they may be suitable. For example, the functional substituent group can be a halogen, an amine, a halogenated compound. Preferably, the functional substituent group can be a halogen. Halogen can make molecules active under electrochemical processes. It is believed that the CC coupling reaction is very likely (if not always) to occur at the halogen substitution position on the precursor, so the halogen substitution promotes the manufacture of polymers. The halogen of the example can be fluorine, chlorine, bromine or iodine. More preferably, the functional substituent group can be bromine or iodine. In a preferred embodiment, the functional substituent group can be iodine. It is not intended to be limited by theory, it is believed that the iodine on the aromatic hydrocarbon substituted by iodine (e.g., compared with bromine) has a larger atomic radius, which causes the covalent bond between iodine and the carbon to which iodine is bonded to be longer. Therefore, the absolute value of the reduction onset potential of iodine-substituted aromatics is generally lower than that of their bromine-substituted counterparts, so iodine-substituted aromatics require a shorter time to form the resulting polymer film. For example, the reduction onset potential of 1,4-diiodobenzene is lower than that of 1,4-dibromobenzene. In another preferred embodiment, the functional substituent group can be bromine. In industrial production, it may be more difficult to prepare iodine-substituted compounds than to prepare their bromine-substituted counterparts, which are more widely used and therefore practically advantageous, although their electrochemical reactivity is relatively low but still acceptable relative to iodine compounds.
[0092] In some cases, the aromatic hydrocarbon used in the method can be selected from the following group: benzene; naphthalene; biphenyl (biphenyl); anthracene; phenanthrene; phenanthene; pyrene; diphenylbenzene (terphenyl); tetracene (i.e., tetracene), triphenylene, Benzene, anthracene, triphenylbenzene and combinations thereof. Other aromatic hydrocarbons may be selected, particularly those polycyclic aromatic hydrocarbons having more benzene rings.
[0093] In one embodiment of the present invention, the aromatic precursor is selected from the group consisting of halogenated benzenes, halogenated polycyclic aromatic hydrocarbons, and combinations thereof. The aromatic precursor includes more than one halogen. In other words, the aromatic precursor may be polyhalogenated rather than monohalogenated. For example, the aromatic precursor may be dihalogenated, trihalogenated, tetrahalogenated, or other polyhalogenated.
[0094] In one embodiment of the present invention, the halogen is selected from the following group: fluorine, chlorine, bromine or iodine and combinations thereof; preferably, the halogen includes bromine or iodine. In one embodiment of the present invention, the aromatic hydrocarbon precursor may be a dihaloaromatic hydrocarbon. The aromatic hydrocarbon precursor may be selected from the following group: dihalobenzene, dihalonaphthalene, dihalobiphenyl, dihaloanthracene, dihalophenanthrene, dihalophenalene, dihalopyrene, dihalodiphenylbenzene, dihalotetracene (i.e., dihalobutylene), dihalotriphenylene, ... dihalogenated benzo[c]phenanthrene, dihalogenated benzo[a]anthracene and combinations thereof; or the aromatic hydrocarbon precursor is selected from the following group: dihalogenated benzene, dihalogenated naphthalene, dihalogenated anthracene, dihalogenated phenanthrene, dihalogenated pyrene and combinations thereof.
[0095] In one embodiment of the present invention, the polymer may be a covalent organic framework (COF). The COF may be two-dimensional (2D). The aromatic precursor of the polymer may be a trisubstituted aromatic. In some cases, the trisubstituted aromatic may be 1,3,5-trisubstituted benzene or 1,3,5-tri(4-substituted phenyl)benzene, such as 1,3,5-trihalobenzene or 1,3,5-tri(4-halophenyl)benzene. In some cases, the aromatic precursor may be 1,3,5-tribromobenzene or 1,3,5-tri(4-bromophenyl)benzene.
[0096] In one embodiment of the present invention, the aromatic hydrocarbon precursor may be a trihaloaromatic hydrocarbon. Optionally, the aromatic hydrocarbon precursor is selected from the group consisting of 1,3,5-trihalobenzene, 1,3,5-tri(4-halophenyl)benzene, and combinations thereof.
[0097] In one embodiment of the present invention, the arene precursor may be a tetrahaloarene. Optionally, the arene precursor comprises 1,3,6,8-tetrahalopyrene.
[0098] In some embodiments of the present invention, the arene precursor may include a mixture of different arenes such that the polymer formed is a heteropolymer.
[0099] In one embodiment of the invention, the aromatic precursor comprises two or more different aromatic precursors. For example, the precursor comprises at least two different disubstituted aromatics, such as dihaloaromatics. Therefore, the manufactured polymer contains at least two types of polymers with different aromatic groups. This allows heterogeneous coupling reactions to occur between different aromatic precursors. In this way, the manufactured polymer with different aromatic groups may be able to show desired or specific optical or electrical properties depending on the application background, which are different from the properties of the polymer film made by the homogeneous coupling reaction involving a single type of precursor. Moreover, the method in some embodiments of the present invention can be applied to heterogeneous coupling reactions to form polymer films, bringing benefits similar to the use of a single type of precursor situation when compared with conventional methods of heterogeneous coupling reactions (such as methods requiring high temperature, harsh pressure or adding precious organic metal catalysts).
[0100] In one embodiment of the invention, the aromatic precursor may include at least two different trisubstituted aromatics. Therefore, the polymer of manufacture contains at least two types of polymers with different aromatic groups, particularly polymers with about three inter-monomer bonds on each monomer. In one embodiment of the invention, the precursor may include at least one trisubstituted aromatic and at least one disubstituted aromatic. For example, the precursor may include trihaloaromatics and dihaloaromatics. In this way, in addition to the above-mentioned difference in nature compared with the situation using a single type of precursor, using different aromatics together as precursors also helps pore size control.
[0101] In one embodiment of the present invention, the precursor can be an unsubstituted precursor. This means that, for example, the precursor is an aromatic hydrocarbon composed of a substantially monocyclic or polycyclic aromatic structure, without any functional group replacing one or more hydrogens on the aromatic structure. In another preferred embodiment of the present invention, the precursor can be a substituted precursor with one or more functional groups, which will not remain in the final polymer product. In other words, one or more substituted functional groups are present in the precursor, and can then be removed in the reaction process of manufacturing the polymer, and therefore may not be included in the polymer manufactured via the reaction. In addition, in some embodiments of the present invention, the manufactured polymer may not contain unwanted side chains. Conventional manufacturing methods (such as usually being carried out at high temperature, severe pressure or adding a noble organic metal catalyst) cause polymers to generally have long side chains, which may adversely change the inherent properties of polymers by changes in the charge density of the main chain, stacking mode and solid-state morphology. Such changes may have a significant impact on their performance in applications such as optical / electronic devices. In contrast, the polymer manufactured according to these embodiments of the present invention omits unwanted side chains.
[0102] In some embodiments of the present invention, the precursor can be a polysubstituted precursor, such as the disubstituted, trisubstituted aromatics or other feasible aromatics discussed above. In one embodiment of the present invention, the aromatic precursor is a dihaloaromatic. The aromatic precursor includes a first halogen and a second halogen. The second halogen is located at a position substantially opposite to the first halogen on the precursor. The dehalogenation reaction occurs at the halogen substitution position. For example, the first dehalogenation reaction occurs at the first halogen, and the second dehalogenation reaction occurs at the second halogen. In the case of dihalobenzene, dehalogenation may occur at the meta or para position. In the case of dihalogen-PAH, the second dehalogenation may occur on a side substantially opposite to the site where the first dehalogenation occurs. For example, in the case of naphthalene, the first dehalogenation may occur at the 1 position of naphthalene, and the second dehalogenation may occur at the 4 or 5 position of naphthalene. In the case of anthracene, the first and second dehalogenations may occur at the 9 and 10 positions of anthracene, respectively, or at the 2 and 6 positions of anthracene. For PAH, the term "substantially opposite" may include not only "directly opposite" situations, such as 1,4-substituted (i.e., para-) benzene, 9,10-substituted anthracene, etc., but also "diagonally opposite" situations, such as 1,3-substituted (i.e., meta-) benzene, 2,6-substituted anthracene, 1,5-substituted naphthalene, etc. Due to the advantage of excellent selectivity, it is desirable to use a halogenated precursor to perform a CC coupling reaction via an electrochemical potential, wherein the coupling reaction preferably occurs at the position where the halogen is substituted.
[0103] In one embodiment of the invention, the aromatic hydrocarbon precursor can be a dihaloaromatic hydrocarbon or a trihaloaromatic hydrocarbon, wherein two or three halogens replace the corresponding hydrogen at the position of the same precursor, so that the distance between these two or three halogens is maximum. The distance between the halogen can be calculated with reference to the numbering system (for example IUPAC numbering system) of aromatic hydrocarbons, wherein each carbon position of aromatic hydrocarbons is numbered. The distance between the halogen can be calculated by the carbon number between the carbon positions where the halogens on aromatic hydrocarbons are located under clockwise / counterclockwise mode. For example, in the case of dihalonaphthalene, when two halogens are respectively located at 1 and 5 of naphthalene, the distance between these two halogens is maximum, so that four carbons are arranged between the positions where these two halogens are located under clockwise or counterclockwise direction. This helps to improve the reaction rate, because this arrangement reduces the steric hindrance during polymerization.
[0104] In one embodiment of the invention, the step of reacting an arene precursor to form a polymer via an electrochemical potential further comprises the step of forming a free radical intermediate of the arene precursor. The arene precursor is used as a halogenated free radical as an intermediate for further forming a polymer (e.g., an aromatic polymer). In the case of a dihaloarene as a precursor, the halogenated free radical can be a monohalogenated free radical. In the case of a trihaloarene, the halogenated free radical can be a dihalogenated free radical.
[0105] As discussed herein, some embodiments of the present invention include the step of reacting an aromatic precursor to produce an aromatic polymer by a dehalogenation carbon-carbon (CC) coupling reaction via an electrochemical potential. Using a disubstituted aromatic hydrocarbon as an example, the reaction can be symbolically represented as X-Ar-X is a precursor and (-Ar-) n is a polymer as the final product. n can be any positive integer, preferably 3 or more. As used herein, "Ar" refers to any aromatic hydrocarbon used to form its corresponding polymer in these embodiments of the present invention. As used herein, "X" refers to a functional group that replaces one or more hydrogens of the aromatic hydrocarbon. For example, "X" refers to a halogen, preferably bromine or iodine. The dot "·" used in conjunction with an element or compound herein represents an element or compound in the form of a free radical, which means that the element or compound contains at least one unpaired electron. For example, "X·" and "Ar·" refer to a functional group (such as a halogen) and a free radical form of a precursor (or monomer), respectively. Similarly, "X-Ar·", "X-Ar-Ar·" and "X-(Ar) n " represents a monohalogenated precursor, or a monohalogenated polymer in dimeric, oligomeric or polymeric form, wherein at one end of the polymer chain is a halogen and at the other end of the polymer chain is an unpaired electron (thus they may be referred to as a monohalogenated free radical). The symbol " - ” refers to the negative charge that is combined with a compound or element after accepting an electron. For example, “X - " refers to a negatively charged halogen. "X-Ar-X - ", "X-Ar-Ar-X - " and "X-(Ar) n -X - " refers to a dihalogenated precursor (or monomer) carrying a negative charge or a dihalogenated polymer in the form of dimerization, oligomerization or polymerization. In the reaction from the precursor to the desired polymer, there may be some double negatively charged intermediates, such as " - X-Ar-X - "," - X-Ar-Ar-X - "and" - X-(-Ar-) n -X - ”, although they are less common. It should be understood that as the reaction proceeds, those halogenated precursors and halogenated polymers (i.e., intermediate polymers) can continue to react in the catalytic cycle to form longer polymer chains.
[0106] In one possible reaction mechanism, Fig.19 As shown in , upon application of an electrochemical potential, the precursor and intermediate polymer are adsorbed on the cathode, and electrons are transferred from the cathode to the adsorbed precursor or direct polymer, which leads to the formation of active intermediates such as “X-Ar-X- ", "X-Ar-Ar-X - " and "X-(-Ar-)nX - "," - X-Ar-X - "," - X-Ar-Ar-X - "and" - X-(-Ar-)nX - ", also known as negatively charged dihaloarene. Subsequently, the bond between the carbon of the aromatic hydrocarbon and the halide (i.e., the CX bond) in the intermediate breaks, producing X-Ar·(and / or X-Ar-Ar·, X-(-Ar-) n -Ar·) and X - . In other words, negatively charged active intermediates can be formed before the halogenated compound is cleaved into free radicals, which is different from other known mechanisms in which the halogenated compound may break and cleave immediately after receiving electrons. Afterwards, two identical or different molecules selected from the group of X-Ar·, X-Ar-Ar· and X-(-Ar-)n-Ar· undergo a CC coupling reaction to form a longer dihalogenated polymer. In some cases, the same two X-Ar· undergo a CC coupling reaction to form X-Ar-Ar-X. In some other cases, X-Ar· and X-Ar-Ar· of different lengths undergo a CC coupling reaction to form X-Ar-Ar-Ar-X. In some cases, the above-generated X-Ar-Ar-X repeats the above steps to react with another X-Ar-X, thereby ultimately forming a conjugated polymer deposited on the surface of the electrode (cathode). It is advantageous to use the method in the embodiment of the present invention to manufacture a polymer film, because the method herein can achieve streamlined "one-stop" manufacturing, wherein during the process, CC coupling reactions and polymer film manufacturing can be achieved simultaneously. On the other hand, some conventional methods require further film processing after polymer synthesis, such as spin coating, casting, etc. Without intending to be limited by theory, it is believed that the method as described in the embodiments of the present invention can allow the direct manufacture of polymer films on substrates (e.g., electrodes as substrates, additional substrates during reactions, or substrates to which the polymer films manufactured are transferred), without any other post-polymerization processing to form films. In other words, the product of the method (i.e., containing aromatic polymers) can be a polymer film formed on the substrate surface during polymerization. By adjusting the reaction parameters, polymer films with desired size, shape, and properties can be obtained.
[0107] In one embodiment of the invention, the step of providing an aromatic precursor further comprises the step of adding the aromatic precursor to the cathode region. The cathode region is separated from the anode region. The above-mentioned feature can be realized, for example, by arranging a separation pool, wherein the cathode region and the anode region are separated into compartments in the pool, both of which contain an electrolyte solution. The cathode electrode and the anode electrode can be immersed in the electrolyte solution in the cathode region and the anode region respectively. The two electrodes are connected by an external circuit from which an electrochemical potential is applied. A semi-permeable membrane can be provided between the anode region and the cathode region, and the semi-permeable membrane allows some molecules to pass through the membrane from one compartment to another compartment or vice versa. The membrane can be, for example, a polymer membrane, such as polyethylene glycol (PEG) polymer, perfluorosulfonic acid (PFSA) polymer or polytetrafluoroethylene (PTFE). A glass sand core filter can also be used as a diaphragm between the anode region and the cathode region.
[0108] In some embodiments of the present invention, the method includes a step of manufacturing a polymer in the form of a film on the surface of a cathode electrode. In particular, the step of reacting an aromatic precursor to form a polymer via an electrochemical potential further includes the step of simultaneously polymerizing the aromatic precursor to form a polymer and forming a film of the polymer on the surface of the cathode electrode. Therefore, compared with conventional methods that require additional film formation processes after polymerization, the simultaneous polymerization and film manufacturing proposed in the embodiments of the present invention are important and highly desirable.
[0109] One of the advantages of adopting the method described in the embodiments of the present invention is that it can realize the accurate control of the thickness of the polymer film so prepared.For example, accurate control can be realized by controlling certain reaction parameters.This thickness depends mainly on synthesis technology and equipment.Equipment shape and size can have some influence on the thickness of film.According to the research of the inventor, the thickness of the film so prepared can be linearly related to the reaction time under constant current.
[0110] The thickness of the polymer film can have a size ranging from nanometer to micrometer. For example, the thickness of the polymer film can reach about 2nm to about 2μm. This strategy without metal / organometallic catalysts can prevent metal / organometallic from being deposited on the surface of the cathode undesirably, thereby ensuring the purity of the film prepared in this way. The method can be used to manufacture large-area thin films and multilayer heterostructures for wide application in organic optoelectronic devices. In one embodiment of the present invention, the electrolyte is selected from the following group: hexafluorophosphate, tetrafluoroborate, ammonium bromide, perchlorate, including but not limited to tetramethylammonium hexafluorophosphate (TMAPF6), tetraethylammonium hexafluorophosphate (TEAPF6), tetrabutylammonium hexafluorophosphate (TBAPF6), potassium hexafluorophosphate (KPF6), tetramethylammonium tetrafluoroborate (TMABF4), tetraethylammonium tetrafluoroborate (TEABF4), tetrabutylammonium tetrafluoroborate (TBABF4), potassium tetrafluoroborate (KBF4), lithium perchlorate (LiClO4) and combinations thereof.
[0111] In one embodiment of the present invention, the solution contains a solvent. For example, the solvent contains an anhydrous organic solvent; optionally, the solvent is selected from the following group: acetone, acetonitrile, toluene, dichloromethane, chloroform, tetrahydrofuran, dimethylformamide, dimethyl sulfoxide, benzonitrile and combinations thereof. In some cases, the solvent contains more than one solvent, such as two solvents or more. For example, the solvent contains acetonitrile and one or more other solvents. In one example, the solvent contains acetonitrile and toluene. More preferably, the amount of acetonitrile is more than the amount of one or more other solvents. In the case where the solvent contains acetonitrile and toluene, the ratio (v / v) of acetonitrile and toluene can be from about 8:1 to about 2:1. In particular, the ratio of acetonitrile to toluene is about 4:1. Film manufacturing depends to some extent on the solubility of the precursor. Using a solution containing a mixed solvent (i.e., containing more than one solvent) can solve the problem of poor solubility of some precursors. In the appropriate electrochemical window, the ratio between solvents does not affect CC bond formation and polymer film preparation. However, containing a larger ratio of acetonitrile (eg, about 8:1 to about 2:1 compared to all other solvents; eg, about 4:1 compared to all other solvents) can provide good conductivity during polymerization, which can shorten the reaction time.
[0112] In one embodiment of the present invention, the dehalogenation coupling reaction can be carried out for about 2 hours to about 36 hours at a constant voltage of about 1.5V to about 3.5V at a temperature of about 0°C to about 60°C or about 10°C to about 35°C. In particular, the voltage can be about 2.3V, about 2.5V, about 2.6V, about 2.8V or about 3.0V. The electrolyte includes tetrabutylammonium hexafluorophosphate at a concentration of about 0.05mmol / mL to about 1mmol / mL. In particular, the electrolyte concentration can be about 0.1mmol / mL. The aromatic precursor concentration can be about 0.001mmol / mL to about 0.5mmol / mL. In particular, the precursor concentration can be about 0.004, about 0.006, about 0.008, about 0.06, about 0.01, about 0.02, about 0.04 or about 0.2mmol / mL.
[0113] In one embodiment of the present invention, the method further comprises the step of adding a quencher to quench the reaction after the step of reacting the aromatic hydrocarbon precursor to form the polymer; optionally, the quencher is selected from the group consisting of water, salt solutions and solvents and combinations thereof.
[0114] In one embodiment of the invention, reacting the aromatic precursor to form a polymer can be carried out at room temperature for about 0.5 hours to about 20 hours at a current density of about 0.5 mA to about 5 mA. A lower current can provide a denser film, but it may require a longer reaction time, and vice versa. In one embodiment of the invention, the method further includes a step of exchanging the positive and negative electrodes of the electrochemical potential to quench the reaction after the step of reacting the aromatic precursor to form a polymer. This can neutralize the electrons accumulated in each double layer to quench the reaction.
[0115] In some embodiments of the present invention, the step of making the aromatic precursor react to form a polymer can be carried out under various pH conditions, for example, under neutral conditions, under alkaline conditions or under slightly acidic conditions. For example, this reaction can be carried out in the pH value range of about 4 to about 14 or about 5 to about 14 or about 6 to about 14 or about 7 to about 14 or about 7 to about 13. Although mentioned in the previous description compared with other conventional methods, the benefit of the embodiment of the method of the present invention is to react successfully under gentle and neutral conditions as under neutral pH conditions, but it is to be understood that this reaction also can be carried out and is practicable under other pH conditions (for example those pH values mentioned above). Preferably, this reaction can be carried out under alkaline conditions, and this may help the aromatic precursor reaction to form an aromatic polymer.
[0116] In one embodiment of the present invention, the method further comprises the step of washing the polymer with a detergent selected from the group consisting of water, ethanol, methanol, n-hexane, 2-dichlorobenzene, dichloromethane, 1,2-dichloroethane, tetrahydrofuran, heptane, ethyl acetate, toluene, acetonitrile and combinations thereof after the step of reacting the aromatic hydrocarbon precursor to form the polymer.
[0117] In one embodiment of the present invention, the method further comprises a step of drying the polymer at a drying temperature of about room temperature to about 250°C, or about room temperature to about 70°C, or about 70°C to about 150°C, or about 80°C to about 100°C after the step of reacting the aromatic precursor to form the polymer; optionally, wherein the drying step is performed under vacuum for a period of about 1 hour to about 12 hours, or about 1 hour to about 6 hours, or about 1 hour to about 4 hours, or about 6 hours to about 12 hours, or about 8 hours to about 12 hours. It is obvious to those skilled in the art that the appropriate time range is selected according to the type and parameters (e.g., thickness) of the polymer film to be dried.
[0118] In one embodiment of the present invention, the anode electrode comprises a conductive substrate; preferably wherein the substrate comprises an inert conductive metal selected from the group consisting of platinum, titanium, alloys thereof, and combinations thereof. The selected anode electrode can provide sufficient voltage to initiate the reaction without dissolving in the solution or depositing on the cathode, in contrast to some active metals, which form cations and dissolve in the solution due to their lower oxidation potential. In addition, active metals can be deposited on the cathode via reduction under cathode bias, which results in impurities in the polymer film, thereby requiring additional processes to remove such deposited metals from the film.
[0119] In one embodiment of the present invention, the cathode electrode comprises a conductive substrate. The cathode electrode may be formed from a group selected from the following: silicon, nickel, gold, platinum, stainless steel, alloys thereof, and combinations thereof. For example, the cathode electrode may comprise silicon.
[0120] One embodiment of the present invention relates to a polymer produced according to the method described in an embodiment of the present invention.
[0121] One embodiment of the present invention relates to a method for producing a chemical composition containing the aromatic polymer, the method comprising the steps of producing the aromatic polymer in the aforementioned embodiment.
[0122] One embodiment of the present invention relates to a chemical composition containing the aromatic polymer produced according to the method described in an embodiment of the present invention.
[0123] General experimental conditions
[0124] Unless otherwise stated, all reactions were performed under nitrogen atmosphere. Toluene, dichloromethane (DCM) and ethanol (EtOH) were purchased from Anaqua Global International Inc. Ltd, Hong Kong, China (http: / / www.anaquahk.com / ) and were ACS grade. Molecular sieves were purchased from Shanghai Aladdin Bio-ChemTechnology Co., Ltd (https: / / www.aladdin-e.com / zh_cn / ), Shanghai, China, activated in a vacuum oven at 300 °C for 3 h, and stored in a glove box. Anhydrous acetonitrile (MeCN) and dimethyl sulfoxide (DMSO) were purchased from J&K Scientific Ltd (Beijing, China). https: / / www.jkchemical.com / ) , and post-activated in a glove box before use The molecular sieves were dried for at least 24 h. Toluene was dried by heating over sodium with benzophenone as an indicator and activated in a glove box before use after adding 10% m / v The electrolyte was purchased from J&K Scientific Ltd (above), recrystallized three times from EtOH, dried in a vacuum oven at 70°C for 24 hours, and stored in a glove box. Unless otherwise specified, all substrates were purchased from TCI (Shanghai) Development Co., Ltd (https: / / www.tcichemicals.com / HK / en / ) in Shanghai, China, and used directly without further purification.
[0125] Fourier transform infrared spectroscopy (FTIR) spectra were obtained on a PerkinElmerSpectrum II from Perkin Elmer Co. (https: / / www.perkin elmer.com) in Waltham, Massachusetts, USA. UV-vis spectroscopy was performed on a UH4150 UV-VIS-NIR spectrophotometer from Hitachi High-Tech Corporation (https: / / www.hitachi-hig htech.com) in Tokyo, Japan. Fluorescence spectroscopy was performed on a FluoroMax-4 from Horiba ltd. Raman spectra were acquired with a WITec alpha300R Raman system. Scanning electron microscopy (SEM) was performed on a Quattro S Environmental SEM from Thermo Fisher Scientific Inc (https: / / www.thermofisher.com) in Waltham, Massachusetts, USA. Atomic force microscopy (AFM) was performed using a MultiMode 8-HR from Bruker Corporation, Billerica, Massachusetts, USA (https: / / www.bruker.com / ).
[0126] Cyclic voltammetry data were measured on a CH Instruments 760E from CH Instruments, Inc., Austin, Texas, USA. A three-electrode electrochemical cell from Gaossunion (Tianjin) Optoelectronics Technology Co., Ltd (http: / / www.gaossunion.com / ) in Wuhan, China, included a 3 mm diameter gold disk as a working electrode, a quasi-reference electrode Ag / AgNO3 containing 0.1 M AgNO3 as a reference electrode, 0.1 M TBAPF6 in acetonitrile as an electrolyte, and a platinum (Pt) wire (37 mm x 0.5 mm) as a counter electrode. The gold disk electrode was polished with a series of alumina powders (1.0 μm, 0.3 μm, and 50 nm) (Tianjin Aida Hengsheng Technology Development Co. Ltd, Tianjin, China, http: / / www.tjaida.cn / ), cleaned with distilled water and acetonitrile, and dried with dry nitrogen before use. Before and after each set of cyclic voltammetry scans, the reference electrode was calibrated against the voltage of ferrocene (1 mM). All measurements were performed at a scan rate of 50 mV / s in pure MeCN solution or MeCN / toluene (v / v=8:2) mixture, or DMSO containing 0.1 M TBAPF6 as a supporting electrolyte. A Pt plate (18 x 12 x 0.2 mm, 99.9% purity, purchased from Taobao.com) was used as an anode and a conductive substrate including silicon, gold, stainless steel, nickel and Pt (18 x 12 mm) was used as a cathode in a DC power supply R4G series from Matsusada Precision Inc (https: / / www.matsusada.com / ) in Shiga, Japan. Reactions were carried out in a two-electrode cell.
[0127] Results and discussion
[0128] In order to explore the possibility of electrochemical dehalogenation carbon-carbon coupling reaction between halogen-substituted benzene / PAH, 1,4-diiodobenzene was first used as an example to polymerize on various planar cathodes under mild and neutral conditions to fabricate poly(p-phenylene) (PPP(I)) thin films. Before polymerization, cyclic voltammetry (CV) was performed on 1,4-diiodobenzene to study its onset potential, which determines the potential window ( Figure 1). According to the CV curve, the onset potential of 1,4-diiodobenzene is about -1.92 V relative to the ferrocene cation / ferrocene (Fc+ / Fc) reference electrode. During the CV scanning process, a light brown color near the cathode surface can be observed, indicating that the IC bond may be broken to form a by-product I2. The film thus prepared was characterized by Fourier transform infrared spectroscopy (FTIR), and several finger peaks of PPP (about 814 and 3026 cm -1 )( Figure 5a Compared with 1,4-diiodobenzene monomer, the CI band (located at 461cm -1 The original vibration peak of the plane disappears, and the characteristic peak of the out-of-plane CH bending vibration appears at 814 cm -1 , indicating that the C-I bond breaks and a para-substituted phenylene moiety is formed. In addition, the vibration of the sp2 hybridized CH on the aromatic ring is -1 The peak at 756 cm -1 and 698cm -1 The other two bands at 100 nm are caused by the terminal monosubstituted phenyl ring and the ring pucker. In addition, Raman spectroscopy further confirmed the formation of the PPP film prepared in this way ( Figure 5b The three peaks in the Raman spectrum (1194, 1285 and 1608 cm -1 ) is the main characteristic band of PPP, which is consistent with the results reported previously. -1 The peak at is attributed to the in-phase stretching of the terminal phenyl ring. Raman image ( Figure 5c ) verified the continuity of the thus prepared PPP film, as the film exhibited uniform intensity in the Raman signal.
[0129] The films have been studied using UV-Vis and fluorescence spectroscopy. The maximum absorption of the PPP film is located at about 345 nm, while the precursor 1,4-diiodobenzene has no such UV absorption in the same range ( Figure 5d The strong fluorescence at 488 nm further confirmed the formation of PPP ( Figure 5d ). In addition, the PPP(I) film thus prepared showed excellent chemical stability and insolubility in many organic solvents including tetrahydrofuran, toluene, dimethylformamide, acetone and chloroform (Figure 2).
[0130] Another advantage of this electrochemical dehalogenation polymerization is that the thickness of the thus prepared film can be easily controlled by adjusting the reaction parameters (e.g., applied voltage, current, reaction time, electrolyte viscosity). -2The relationship between the thickness and the reaction time at the current density is shown in Figure 3. Taking the silicon cathode as an example, the thickness of the PPP(I) film increases linearly with the extension of the reaction time ( Figure 3f ), and the theoretical minimum thickness of the PPP(I) film can reach, for example, about 30 nm. However, when the reaction time is extended to more than 5 hours, the PPP(I) film may reach its maximum thickness because horizontal crack lines and dislocations ( Figure 3d and Figure 3e ). In addition, the thickness of the underlying PPP(I) film (measured from the crack line to the substrate) is Figure 3d The SEM images show that the films prepared in this way show a continuous and compact morphology compared with PPP films prepared by other methods. The corresponding EDX mapping also shows that the film grows uniformly on the substrate ( Figure 6a and 6b In addition, the smooth surface of the PPP(I) film prepared in this way was also characterized by atomic force microscopy (AFM), in which the root mean square roughness Rq was only 11.9 nm ( Figure 7a and 7b ).
[0131] Without intending to be limited by theory, it is believed that the electrochemical deposition strategy allows the direct fabrication of PPP(I) thin films of different sizes and shapes under the same conditions by conveniently pre-patterning the conductive substrate ( FIGS. 4 and Figure 5d ). It is worth noting that, in contrast to the anodic oxidation strategy, which always suffers from the disadvantage of substrate limitation (e.g., most active metals are not suitable as electrodes due to their lower oxidation potential), the electrons accumulated at the cathode give the metal electrode a significant negative potential, thereby protecting the metal electrode from oxidation to form soluble cations. This makes it possible to fabricate conjugated polymer membranes on a variety of metal substrates. As mentioned, the coupling reaction occurs under cathode bias, so polymerization still occurs after the platinum anode is replaced with other sacrificial anodes (i.e., iron and zinc). Surprisingly, the solvent does not significantly affect the electrochemical dehalogenation CC coupling reaction, because the formation of new CC bonds between aromatic monomers can be achieved in a variety of solvents, including MeCN, DMF, DMSO, and especially MeCN / toluene mixtures (Table 1). Other conditions are summarized in Table 1. In addition, due to the additive- and catalyst-free strategy, it is feasible to prepare PPP membranes on different conductive substrates, but necessary optimization of the reaction conditions is required (Figure 4).
[0132] Other conditions for aggregation:
[0133] Table 1 Deviations from standard conditions
[0134]
[0135] a Adding TEA or DIPEA can increase the reaction rate. b Different solvents with wide electrochemical windows may not affect the formation of polymer films, but the reaction times are different (i.e., 3 h and 8 h for DMF and DMSO, respectively). c The conductivity can be significantly reduced in high ratio toluene systems where polymerization takes longer. d High voltage may not affect polymerization, but a continuous film cannot be obtained at the cathode. e The voltage is in the range of 2 to 2.8 V. A continuous film may not be obtained at a high constant current.
[0136] The successful polymerization of 1,4-diiodobenzene via electrochemical dehalogenation strongly motivated us to extend our research scope to other halogen-substituted aromatic compounds ( Figures 18a-18j As one of the typical bromine-substituted benzenes, 1,4-dibromobenzene (1,4-DBB) was selected as the precursor, which was successfully polymerized under similar conditions except for prolonged reaction time to form the corresponding membrane ( Figure 8a-8c ). It should be noted that bromine-substituted aromatic compounds generally require more negative reduction potentials due to the higher bond energy of Ar-Br compared to Ar-I. In addition, a series of halogen-substituted PAHs (i.e., 1,4-dibromonaphthalene (1,4-DBN) ( Figure 9a-9c and Figure 10a-10c )、1,5-dibromonaphthalene (1,5-DBN) ( Figure 11a-11b )、9,10-dibromoanthracene (9,10-DBA) ( Figure 12a-12b )、2,6-dibromoanthracene (2,6-DBA) ( Figure 13a-13b )、2,7-Dibromophenanthrene (2,7-DBP) ( Figure 14a-14b ) and 2,7-dibromopyrene (2,7-DBPy) ( Figure 15a-15b )) and the precursors of two-dimensional (2D) covalent organic frameworks (COFs) (i.e., 1,3,5-tribromobenzene (TBB) ( Figures 16a-16d ) and 1,3,5-tris(4-bromophenyl)benzene)(TBPB)( Figures 17a-17d ) have been successfully polymerized via electrochemical dehalogenation CC coupling reactions. Notably, weakly alkaline conditions (i.e., addition of triethylamine or N,N-diisopropylethylamine) significantly increased the reaction rate without sacrificing the quality of the membranes so prepared. However, chlorine- and fluorine-substituted aromatic compounds rarely gave positive results, probably due to the higher bond energies of Ar-Cl and Ar-F. After polymerization, all membranes were characterized by various spectra and showed finger-like peaks: PPP(Br) (FTIR: ca. 820 cm -1; Raman: 1001, 1289 and 1607 cm -1 )、Poly(1,4-naphthalene)(1,4-PN)(FTIR: 842 and 774 cm -1 ), poly(1,5-naphthalene)(1,5-PN)(FTIR: 795 and 775 cm -1 ); poly(9,10-anthracene) (9,10-PA) (FTIR: 746, and 880 cm -1 disappearance), poly(2,6-anthracene)(2,6-PA)(FTIR: 885 and 802 cm -1 )、Poly(2,7-phenanthrene)(2,7-PPA)(FTIR: 888, 810 and 740 cm -1 )、Poly(2,7-pyrene)(2,7-PPy)(FTIR: 879 and 818 cm -1 )、1,3,5-polyphenylene (PTBB) (FTIR: about 887, 756 and 698 cm -1 ; Raman: 1001, 1300 and 1602 cm -1 ) and poly(1,3,5-triphenylbenzene) (PTBPB) (FTIR: 881 and 820 cm -1 ; Raman: 1001, 1346 and 1608 cm -1 ). In addition, UV-vis absorption of all films has been performed, such as Figures 18b-18j As shown in: the maximum absorption is located at 328nm for PPP(Br), 355nm for 1,4-PN, 320nm for 1,5-PN, 391nm for 9,10-PA, 296nm for 2,6-PA, 330nm for 2,7-PPA, 385nm for 2,7-PPy, 293nm for PTBB, and 322nm for PTBPB membrane. It is worth pointing out that although a larger degree of conjugation can stabilize the aromatic part and significantly reduce the potential required for the coupling reaction, this is not absolute, because in fact some sites substituted by halogens may be relatively less active (Table 2). Interestingly, although there are some differences in the onset potentials between the isomers, the proposed strategy provides good site selectivity, which is not achievable via traditional anodic coupling reactions. For example, the polymerization of 1,4-DBN occurs at positions 1 and 4, and the carbon-carbon coupling reaction of 1,5-DBN occurs at positions 1 and 5, which supports the high selectivity at the halogen-substituted positions. Similar results were found in the electrochemical polymerization of 9,10-dibromoanthracene (9,10-DBA) and 2,6-dibromoanthracene (2,6-DBA), which also supports the good site selectivity of the proposed electrochemical dehalogenation CC coupling strategy ( Figure 12a-12b and Figure 13a-13b). All these results clearly demonstrate that simultaneous polymerization of benzene / PAH and membrane fabrication via electrochemical dehalogenation CC coupling reaction is feasible.
[0137] Table 2. Onset potentials of halogen-substituted precursors.
[0138]
[0139] in conclusion
[0140] In summary, the electrochemical dehalogenation CC coupling strategy for simultaneously polymerizing halogen-substituted aromatic compounds and forming smooth films on various planar cathodes has been successfully demonstrated, in which electrons can directly act as catalysts. This strategy without metal / organometallic catalysts can prevent metal / organometallics from being undesirably deposited on the surface of the cathode, thereby ensuring the purity of the film prepared in this way. It is worth noting that this electrochemical dehalogenation CC coupling method provides excellent selectivity, in which the coupling reaction can occur at the position of halogen substitution. The formation of polymers at cathode potential during electrolysis shows many advantages, such as different conductive substrates (i.e., platinum, gold, nickel, silicon and stainless steel) can be used. In addition, the thickness of the film prepared in this way can be easily controlled by adjusting the reaction time at a certain current level. We believe that the size and shape of the film prepared in this way directly depend on various conductive substrates. We believe that this electrochemical dehalogenation CC coupling strategy will be extended to establish carbon-carbon bonds between aromatic compounds containing heteroatoms (e.g., N, S, O or P). In addition, this strategy will become a powerful tool for the simultaneous construction of carbon-carbon bonds in 1D, 2D or 3D organic frameworks and the fabrication of smooth semiconductor films. Obviously, the films so fabricated should have great advantages in various organic optoelectronic devices.
[0141] Example 1
[0142] Preparation of poly(p-phenylene)(II)
[0143]
[0144] Under nitrogen atmosphere, 1mmol TBAPF6 was dissolved in 10mL dry MeCN (ie, the concentration of TBAPF6 was 0.1mmol / mL) and evenly divided into two parts marked as solution A and solution C. 1,4-diiodobenzene (0.1mmol) was added to solution C (ie, the concentration of 1,4-diiodobenzene was 0.02mmol / mL), and pre-stirred for about 5 minutes to obtain a uniform solution. Then the resulting solution A and solution C containing diiodobenzene were added to the anode part and cathode part of a flame-dried divided cell equipped with Pt (anode) and Si (cathode or other conductive substrate), respectively. Afterwards, the electrolyte cell was sealed and removed from the glove box to polymerize for about 5 hours via an electrochemical dehalogenation CC coupling reaction at room temperature and a constant voltage of 2.5V. After the reaction, the cathode was carefully removed from the solution, gently immersed in a sample bottle filled with toluene, and washed several times with toluene, DCM, EtOH and water. The film was then pre-dried in air before being transferred to a vacuum oven (100°C) for further drying. FTIR spectra were recorded on a PerkinElmer Spectrum Two FTIR spectrometer. Figure 5a Compared with its precursor, the -1 The typical band of CI vibration at 814 cm-1 disappears, while the indicative out-of-plane CH bending vibration appears at 814 cm-1. -1 At 756 cm -1 and 698cm -1 The other two bands at are attributed to the terminal monosubstituted phenyl ring and ring collapse. The procedure for preparing PPP films using 1,4-dibromobenzene as the starting material was almost the same, but the reaction time was extended (24 h at a constant voltage of 2.8 V). It is worth noting that the use of an organic base (i.e., the addition of 3 equivalents of triethylamine or N,N-diisopropylethylamine) can significantly shorten the reaction time to 12 h without sacrificing the film quality. The FTIR spectrum of 1,4-dibromobenzene is shown in Figure 8b Medium. At 825cm -1 The peak indicating para-substitution appears at 1064 cm -1 and 470cm -1 The disappearance of the C-Br vibration at , together with the disappearance of the C-Br vibration at , confirms the formation of PPP(Br).
[0145] Example 2
[0146] Preparation of 1,5-polynaphthalene (III)
[0147]
[0148] Under a nitrogen atmosphere, 1 mmol of TBAPF6 was dissolved in 10 mL of dry MeCN and evenly divided into two parts marked as solution A and solution C. 1,5-Dibromonaphthalene (0.1 mmol) was added to solution C and pre-stirred for about 5 minutes to obtain a uniform solution. The resulting solution A and solution C containing dibromonaphthalene were then added to the anode and cathode parts of a flame-dried separated battery equipped with Pt (anode) and Si (cathode or other conductive substrate), respectively. Afterwards, the electrolyte cell was sealed and taken out of the glove box to polymerize via an electrochemical dehalogenation CC coupling reaction at room temperature and a constant voltage of 2.8 V for about 8 hours. After the reaction, the cathode was carefully removed from the solution, gently immersed in a sample bottle filled with toluene, and washed several times with toluene, DCM, EtOH, and water. The membrane was then pre-dried in air before being transferred to a vacuum oven (80°C) for further drying. As Fig.11b As shown in FIG. , the 1,5-PN thus prepared retains the -1 The strong band at 559 cm -1 The decrease of C-Br vibration and ring fold at 700 cm-1 of 1,5-DBN -1 The 737 cm -1 The shift of supports the coupling occurs at positions 1 and 5. In addition, the indicative vibration of three adjacent CH swings from 789 cm -1 To 795cm -1 The displacement and the -1 The broad absorption peaks in the range support the successful electropolymerization.
[0149] Example 3
[0150] Preparation of 1,4-polynaphthalene (IV)
[0151]
[0152] Under a nitrogen atmosphere, 1 mmol of TBAPF6 was dissolved in 10 mL of dry MeCN and evenly divided into two parts labeled solution A and solution C. 1,4-Dibromonaphthalene (0.1 mmol) was added to solution C and pre-stirred for about 5 minutes to obtain a uniform solution. The resulting solution A and solution C containing dibromonaphthalene were then added to the anode and cathode parts of a flame-dried separated battery equipped with Pt (anode) and Si (cathode), respectively. Afterwards, the electrolyte cell was sealed and taken out of the glove box to polymerize via an electrochemical dehalogenation CC coupling reaction at room temperature and a constant voltage of 2.8 V for about 3 hours. After the reaction, the cathode was carefully removed from the solution, gently immersed in a sample bottle filled with toluene, and washed several times with toluene, DCM, EtOH, and water. The membrane was then pre-dried in air before being transferred to a vacuum oven (80°C) for further drying. The FTIR spectrum is shown in Figure 9b Medium. 774cm -1 The wider band nearby is the specific structural vibration of naphthalene. The second strongest peak appears at 842 cm -1 , which represents the swing of two adjacent CH on the naphthalene ring, indicating that polymerization occurs at positions 1 and 4. In addition, compared with the precursor, the 540 cm -1 The band at position 1 is much lower, indicating a decrease in the C-Br ratio in the film, which indirectly proves that the polymerization occurs at positions 1 and 4.
[0153] Example 4
[0154] Preparation of 9,10-polyanthracene (VII)
[0155]
[0156] Under nitrogen atmosphere, 1 mmol TBAPF6 was dissolved in 10 mL of dry MeCN / toluene mixture (v / v=8:2) and evenly divided into two parts marked as solution A and solution C. 9,10-dibromoanthracene (0.1 mmol) was added to solution C and pre-stirred for about 5 minutes to obtain a uniform solution. The resulting solution A and dibromoanthracene solution C were then added to the anode and cathode parts of the flame-dried separated battery equipped with Pt (anode) and Si (cathode), respectively. Afterwards, the electrolyte cell was sealed and removed from the glove box to polymerize for about 8 hours via an electrochemical dehalogenation CC coupling reaction at room temperature and a constant voltage of 2.3 V. After the reaction, the cathode was carefully removed from the solution, gently immersed in a sample bottle filled with toluene, and washed several times with toluene, DCM, EtOH, and water. Then, the membrane was pre-dried in air before being transferred to a vacuum oven (80°C) for further drying.
[0157] Example 5
[0158] Preparation of 2,6-polyanthracene (VIII)
[0159]
[0160] Under a nitrogen atmosphere, 1 mmol of TBAPF6 was dissolved in 10 mL of a dry MeCN / toluene mixture (v / v=8:2) and evenly divided into two parts labeled solution A and solution C. 2,6-Dibromoanthracene (0.1 mmol) was added to solution C and pre-stirred for about 5 minutes to obtain a uniform solution. The resulting solution A and solution C containing dibromoanthracene were then added to the anode and cathode parts of a flame-dried separated battery equipped with Pt (anode) and Si (cathode), respectively. Afterwards, the electrolyte cell was sealed and removed from the glove box to polymerize via an electrochemical dehalogenation CC coupling reaction at room temperature and a constant voltage of 2.5 V for about 8 hours. After the reaction, the cathode was carefully removed from the solution, gently immersed in a sample bottle filled with toluene, and washed several times with toluene, DCM, EtOH, and water. The membrane was then pre-dried in air before being transferred to a vacuum oven (80°C) for further drying. As Fig.13b The FTIR spectra of the 2,6-PA film, anthracene monomer and 2,6-dibromoanthracene prepared in this way are shown in FIG. 9 and 10 are retained, which is indicated by the presence of a -1 The same two adjacent CH swing absorptions towards 802 cm -1 The displacement together with 540cm -1 The disappearance of the C-Br vibration at 739 cm strongly confirms that the coupling reaction occurs at the 2- and 7-positions occupied by bromine. -1 The nearby bands are attributed to four adjacent CH swings.
[0161] Example 6
[0162] Preparation of 2,7-polyphenanthrene (X)
[0163]
[0164] Under a nitrogen atmosphere, 1 mmol of TBAPF6 was dissolved in 10 mL of a dry MeCN / toluene mixture (v / v=8:2) and evenly divided into two parts labeled solution A and solution C. 2,7-Dibromophenanthrene (0.1 mmol) was added to solution C and pre-stirred for about 5 minutes to obtain a uniform solution. The resulting solution A and solution C were then added to the anode and cathode parts of a flame-dried, separated battery equipped with Pt (anode) and Si (cathode), respectively. Afterwards, the electrolyte cell was sealed and removed from the glove box to polymerize via an electrochemical dehalogenation CC coupling reaction at room temperature and a constant voltage of 2.5 V for about 12 hours. After the reaction, the cathode was carefully removed from the solution, gently immersed in a sample bottle filled with toluene, and washed several times with toluene, DCM, EtOH, and water. The membrane was then pre-dried in air before being transferred to a vacuum oven (80°C) for further drying. As Fig.14b As shown in Figure 2, the indicative two adjacent CH swings from 795 cm of 2,7-DBP -1 Towards 810cm of 2,7-PPA -1 The shift of 888cm represents the departure of bromine. -1 The band at 877 cm is usually indicative of isolated CH swing in meta- or 1,2,4-trisubstituted benzenes, which is consistent with the 877 cm of 2,7-DBP. -1 In addition, compared with the 2,7-DBP spectrum, the -1 There are broad bands nearby that are attributed to the collapse of the meta- or 1,2,4-trisubstituted phenyl rings, indicating that polymerization occurs at the 2- and 7-positions.
[0165] Example 7
[0166] Preparation of 2,7-polypyrene (XII)
[0167]
[0168] Under a nitrogen atmosphere, 1 mmol of TBAPF6 was dissolved in 10 mL of a dry MeCN / toluene mixture (v / v=8:2) and evenly divided into two parts labeled solution A and solution C. 2,7-Dibromopyrene (0.04 mmol) was added to solution C and pre-stirred for about 5 minutes to obtain a uniform solution. The resulting solution A and solution C were then added to the anode and cathode parts of a flame-dried, separated battery equipped with Pt (anode) and Si (cathode), respectively. Afterwards, the electrolyte cell was sealed and removed from the glove box to polymerize via an electrochemical dehalogenation CC coupling reaction at room temperature and a constant voltage of 2.5 V for 8 hours. After the reaction, the cathode was carefully removed from the solution, gently immersed in a sample bottle filled with toluene, and washed several times with toluene, DCM, EtOH, and water. The membrane was then pre-dried in air before being transferred to a vacuum oven (80°C) for further drying. As Fig.15b As shown in the figure, 700cm -1 Compared with the commercially available pyrene monomer (purchased from Sigma-Aldrich), the spectrum of the 2,7-PPy film prepared in this way shows almost no band at 746 cm-1, which is attributed to the out-of-plane vibration of three adjacent CH bonds of the pyrene ring. -1 However, the 2,7-PPy film prepared in this way has a band at 818 cm -1 The band at 879 cm-1 is much stronger, which can be attributed to the swinging of two adjacent CHs of the pyrene ring. -1 The band at 859 cm represents the isolated CH swing near the 2- and 7-positions, which is consistent with the 859 cm -1 In addition, the 500cm -1 The reduction of the C-Br bond at together with the shift of the isolated and two adjacent C-H swings supports the successful fabrication of 2,7-PPy thin films.
[0169] Example 8
[0170] Preparation of 1,3,5-polyphenylene (PTBB)
[0171]
[0172] In a nitrogen-filled glove box, 1 mmol of TBAPF6 was dissolved in 10 mL of dry DMSO and evenly divided into two parts labeled solution A and solution C. 1,3,5-Tribromobenzene (0.1 mmol) and 3 equivalents of N,N-diisopropylethylamine (DIPEA) were added to solution C and pre-stirred for about 5 minutes to obtain a uniform solution. Then, solution A and solution C containing tribromobenzene were added to the anode part and cathode part of the flame-dried divided cell (equipped with Pt (anode) and Si (cathode)), respectively. After that, the electrolyte cell was sealed and removed from the glove box to polymerize for about 24 hours via an electrochemical dehalogenation CC coupling reaction at room temperature and a constant voltage of 3.0 V. After the reaction, the cathode was carefully removed from the solution, gently immersed in a sample bottle filled with toluene, and washed several times with toluene, DCM, EtOH and water. Then, the membrane was pre-dried in air, after which the membrane was transferred to a vacuum oven (100°C) for further drying.
[0173] Example 9
[0174] Preparation of poly(1,3,5-triphenylbenzene) (PTBPB)
[0175]
[0176] In a nitrogen-filled glove box, 1 mmol of TBAPF6 was dissolved in 10 mL of dry DMSO and evenly divided into two parts labeled solution A and solution C. 1,3,5-tri(4-bromophenyl)benzene (0.03 mmol) and 3 equivalents of DIPEA were added to solution C and pre-stirred for about 15 minutes to obtain a uniform solution. Then, solution A and solution C containing tri(bromophenyl)benzene were added to the anode and cathode parts of a flame-dried divided cell (equipped with Pt (anode) and Si (cathode)), respectively. After that, the electrolyte cell was sealed and removed from the glove box to polymerize for about 24 hours via an electrochemical dehalogenation CC coupling reaction at room temperature and a constant voltage of 3.0 V. After the reaction, the cathode was carefully removed from the solution, gently immersed in a sample bottle filled with toluene, and washed several times with toluene, DCM, EtOH, and water. Then, the membrane was pre-dried in air, after which the membrane was transferred to a vacuum oven (100°C) for further drying.
[0177] Example 10
[0178] Electrochemical cell setup
[0179] Fig.21a A simplified diagram of an electrochemical cell useful for carrying out the method of the present invention is shown, showing the arrangement of two outer metal plates and two intermediate plates.
[0180] Figure 21b A schematic cross-sectional view of an electrochemical cell 10 with other components is shown. Two outer metal plates 24 are provided, between which two mutually superposed intermediate plates 28 are provided, and each intermediate plate 28 contains a central cavity. A membrane 34 is provided between the two intermediate plates 28. A cathode electrode 38 is provided between one of the outer metal plates (i.e., the left metal plate) 24 and one of the intermediate plates (i.e., the left intermediate plate) 28. An anode electrode 22 is provided between another outer metal plate (i.e., the right metal plate) 24 and another intermediate plate (i.e., the right intermediate plate) 28. A cathode region 36 is provided, and is defined by the left metal plate 24, the left intermediate plate 28, and the membrane 30. The cathode electrode 38 is located at the cathode region 36. An anode region 20 is provided, and is defined by the right metal plate 24, the right intermediate plate 28, and the membrane 30. The anode electrode 22 is located at the anode region 20. There are a plurality of openings on the top side of the intermediate plate 28. A reference electrode 30 is inserted from the outside into the cavity of the intermediate plate 28 from one of the openings. The spacers 32 are placed on both sides of each intermediate plate 28 facing the metal plate 24. The current collector 26 is placed on top of each metal plate 24. This arrangement allows the electrode to be in good contact with the precursor and the polymer film. It also allows for uniform current density on the electrode when manufacturing polymer films (including large-scale films with a scaled-up version of this design).
[0181] Embodiment 11
[0182] Transfer of the film thus obtained
[0183] In this case, the capillary force assisted clean stamp transfer method was used to transfer the two-dimensional film to different substrates for other characterizations. In brief, the PDMS stamp was prepared by mixing Sylgard and hardener (Dow Corning, 184 silicone elastomer kit) in a ratio of 9: 1. The glass slide was cleaned with acetone and isopropanol under ultrasonication and placed in a clean petri dish before pouring the mixed PDMS solution. The mixture was placed in a vacuum box for about 1.5 hours to ensure that all bubbles in the solution were removed. The PDMS mixture was then baked at 50°C for 12 hours. The prepared PDMS membrane was cut into the required size, cleaned with isopropanol, DI water, and dried before use. The PDMS stamp was placed on top of boiling water for a few seconds and then gently pressed onto the film prepared in this way. Leave a few seconds for the film to relax and peel it off from one side. The transferred film was stored in a clean container for further transfer to other substrates. A simple stamping procedure was sufficient to leave the film on other substrates. Alternatively, tearing the film directly off the substrate with tweezers can also be used to transfer films with micrometer thickness.
[0184] Non-limiting embodiments of the present invention:
[0185] A method for producing an aromatic polymer comprising the steps of:
[0186] a) providing an anode region and a cathode region;
[0187] b) providing an aromatic hydrocarbon precursor;
[0188] c) providing an electrochemical potential between the anode region and the cathode region;
[0189] d) reacting the aromatic hydrocarbon precursor via the electrochemical potential to form the polymer, wherein the reacting step d) further comprises the step of performing a cathode reaction.
[0190] 2. The method according to embodiment 1, wherein the cathode reaction further comprises the step of performing a dehalogenation coupling reaction of the aromatic hydrocarbon precursor to form the polymer.
[0191] 3. A method according to embodiment 1 or 2, wherein the method further comprises the step of providing an anode electrode at the anode region, a cathode electrode at the cathode region, and a solution containing an electrolyte, wherein the anode electrode and the cathode electrode are at least partially in contact with the solution.
[0192] 4. The method of any one of embodiments 1 to 3, wherein the aromatic polymer is a conjugated polymer; optionally, the aromatic polymer is an unsubstituted conjugated polymer.
[0193] 5. The method according to any one of embodiments 1 to 4, wherein the aromatic polymer is in a form selected from the group consisting of a dimeric form, an oligomeric form, a polymeric form, and combinations thereof.
[0194] 6. The method according to any one of embodiments 1 to 5, wherein the aromatic hydrocarbon precursor is selected from the group of halogenated benzenes, halogenated polycyclic aromatic hydrocarbons, and combinations thereof, and wherein the aromatic hydrocarbon precursor comprises more than one halogen.
[0195] 7. According to the method according to any one of embodiments 1 to 6, the halogen is selected from the group consisting of fluorine, chlorine, bromine or iodine and combinations thereof; preferably, the halogen comprises bromine or iodine.
[0196] 8. The method according to any one of embodiments 1 to 7, wherein the aromatic hydrocarbon precursor is a dihaloaromatic hydrocarbon, optionally, the aromatic hydrocarbon precursor is selected from the group consisting of dihalobenzene, dihalonaphthalene, dihalobiphenyl, dihaloanthracene, dihalophenanthrene, dihalophenalene, dihalopyrene, dihalodiphenylbenzene, dihalotetracene, dihalotriphenylene, dihalo Dihalogenated benzo[c]phenanthrene, dihalogenated benzo[a]anthracene and combinations thereof.
[0197] 9. A method according to any one of embodiments 1 to 8, wherein the aromatic hydrocarbon precursor comprises a first halogen and a second halogen, wherein the second halogen is located at a position on the precursor substantially opposite to the first halogen, and the dehalogenation reaction occurs at the halogen substitution position.
[0198] 10. The method of any one of embodiments 1 to 9, wherein the aromatic polymer forms a covalent organic framework.
[0199] 11. The method according to any one of embodiments 1 to 10, wherein the aromatic hydrocarbon precursor is a trihaloarene; optionally, wherein the aromatic hydrocarbon precursor is selected from the group consisting of 1,3,5-trihalobenzene, 1,3,5-tris(4-halophenyl)benzene, and combinations thereof.
[0200] 12. The method of any one of embodiments 1 to 11, wherein the arene precursor is a tetrahaloarene, optionally wherein the arene precursor comprises 1,3,6,8-tetrahalopyrene.
[0201] 13. A method according to any one of embodiments 1 to 12, wherein the aromatic hydrocarbon precursor is a dihaloarene or a trihaloarene, and wherein two or three halogens replace the corresponding hydrogens at the positions of the same aromatic hydrocarbon precursor so that the distance between the two or three halogens is maximized.
[0202] 14. The method according to any one of embodiments 1 to 13, wherein the reacting step d) further comprises the step of causing the aromatic hydrocarbon precursor to form a free radical intermediate to form the polymer.
[0203] 15. The method of any one of embodiments 1 to 14, wherein the aromatic hydrocarbon precursor comprises two or more different aromatic hydrocarbon precursors.
[0204] 16. The method according to any one of embodiments 1 to 15, wherein the step b) of providing the aromatic hydrocarbon precursor further comprises the step of adding the aromatic hydrocarbon precursor to the cathode region, wherein the cathode region is separate from the anode region.
[0205] 17. The method according to any one of embodiments 1 to 16, wherein the reaction step d) further comprises the steps of simultaneously polymerizing the aromatic hydrocarbon precursor to form a polymer and forming a film of the polymer on the surface of the cathode electrode.
[0206] 18. A method according to any one of embodiments 1 to 17, wherein the electrolyte is selected from the following group: hexafluorophosphate, tetrafluoroborate, ammonium bromide, perchlorate and combinations thereof; optionally, the electrolyte is selected from the following group: tetramethylammonium hexafluorophosphate (TMAPF6), tetraethylammonium hexafluorophosphate (TEAPF6), tetrabutylammonium hexafluorophosphate (TBAPF6), potassium hexafluorophosphate (KPF6), tetramethylammonium tetrafluoroborate (TMABF4), tetraethylammonium tetrafluoroborate (TEABF4), tetrabutylammonium tetrafluoroborate (TBABF4), potassium tetrafluoroborate (KBF4), lithium perchlorate (LiClO4) and combinations thereof.
[0207] 19. The method of any one of embodiments 1 to 18, wherein the solution further comprises a solvent; optionally, wherein the solvent comprises an anhydrous organic solvent; optionally, the solvent is selected from the group consisting of acetone, acetonitrile, toluene, dichloromethane, chloroform, tetrahydrofuran, dimethylformamide, dimethyl sulfoxide, benzonitrile, and combinations thereof.
[0208] 20. The method of any one of embodiments 1 to 19, wherein the solvent comprises acetonitrile and toluene; optionally, wherein the ratio of acetonitrile to toluene is from about 8:1 to about 2:1; optionally, the ratio of acetonitrile to toluene is about 4:1.
[0209] 21. The method according to any one of embodiments 1 to 20, wherein the dehalogenation coupling reaction is carried out at a temperature of about 0°C to about 60°C and a constant voltage of about 1.5V to about 3.5V for about 2 hours to about 36 hours.
[0210] 22. A method according to any one of embodiments 1 to 21, wherein the electrolyte comprises tetrabutylammonium hexafluorophosphate at a concentration of about 0.05 mmol / mL to about 1 mmol / mL, and wherein the aromatic hydrocarbon precursor concentration is about 0.001 mmol / mL to about 0.5 mmol / mL.
[0211] 23. The method according to any one of embodiments 1 to 22, further comprising the step of adding a quenching agent to quench the reaction after the reaction step d); optionally, the quenching agent is selected from the group consisting of water, a salt solution and the solvent and combinations thereof.
[0212] 24. The method according to any one of embodiments 1 to 23, further comprising the step of exchanging the positive and negative poles of the electrochemical potential to quench the reaction after the reacting step d).
[0213] 25. The method according to any one of embodiments 1 to 24, further comprising a step f) of washing the polymer after the reacting step d) with a washing agent selected from the group consisting of water, ethanol, methanol, n-hexane, 2-dichlorobenzene, dichloromethane, 1,2-dichloroethane, tetrahydrofuran, heptane, ethyl acetate, toluene, acetonitrile and combinations thereof;
[0214] 26. A method according to any one of embodiments 1 to 25, wherein the method includes a step of drying the polymer after the reacting step d) at a drying temperature of about room temperature to about 250°C, or about room temperature to about 70°C, or about 70°C to about 150°C, or about 80°C to about 100°C; optionally, wherein the drying step is carried out under vacuum for a period of about 1 hour to about 12 hours, or about 1 hour to about 6 hours, or about 1 hour to about 4 hours, or about 6 hours to about 12 hours, or about 8 hours to about 12 hours.
[0215] 27. A method according to any one of embodiments 1 to 26, wherein the anode electrode comprises a conductive substrate; preferably wherein the substrate comprises an inert conductive metal selected from the group of platinum, titanium, alloys thereof, and combinations thereof.
[0216] 28. The method of any one of embodiments 1 to 27, wherein the cathode electrode comprises a conductive substrate selected from the group consisting of silicon, nickel, gold, platinum, stainless steel, alloys thereof, and combinations thereof.
[0217] 29. A polymer produced according to the method of any one of embodiments 1 to 28.
[0218] It should be understood that the foregoing merely illustrates and describes embodiments in which the present invention may be implemented and that modifications and / or variations may be made thereto without departing from the spirit of the present invention.
[0219] It should also be understood that certain features of the present invention described in the context of separate embodiments for clarity may also be provided in combination in a single embodiment. Conversely, various features of the present invention described in the context of a single embodiment for brevity may also be provided separately or in any suitable sub-combination.
[0220] All references specifically cited herein are hereby incorporated by reference in their entirety. However, citation or incorporation of such a reference is not necessarily an admission of its appropriateness, applicability, and / or applicability as prior art / for the present invention.
[0221] References
[0222] 1.Kong,J.et al.Long-term stable polymer solar cells withsignificantly reduced burn-in loss.Nat.Commun.5,5688(2014).
[0223] 2.Garg,S.&Coel,N.Optoelectronic applicatious of conjugated organicpolymers:influence of donor / acceptor groups through density functionalstudies.J.Phys.Chem.C 126,9313-9323(2022).
[0224] 3.Wu,X.et al.Wearable in-Sensor reservoir computing uslingoptoelectronic polymers with through-space charge-transport characteristicsfor multi-task learning.Nat.Commun.14,468(2023).
[0225] 4.Yin,J.et al. Programmable zigzagπ-extension toward graphene-likemolecules by the stacking of naphthalene blocks.Nat.Synth.(2023)doi:10.1038 / s44160-023-00306-6.
[0226] 5.Cheng,L.et al.Steering the topological defects in amorphous laser-induced graphene for direct nitrate-to-ammonia eleetroreduction.ACS Catal.12,11639-11650(2022).
[0227] 6.Cheng,Y.,Yang,S.&Hsu,C.Synthcsis of conjugated polymers for organicsolar cell applications.Chem.Rev.109,5868-5923(2009).
[0228] 7.Ullmann,F.&Bielecki,J.Ueber synthesen in der biphenylreihe.Ber.Dtsch.Chem.Ges.34,2174-2185(1901).
[0229] 8.Zhou,D.,Tan,X.,Wu,H.,Tian,L.&Li,M.Synthesis of C-C bonded two-dimensional conjugated covalent organic framework films by Suzukipolymerization on a liquid-liquid interface.Angew.Chem.Int.Ed.131,1390-1395(2019).
[0230] 9.Wang,D.&Li,M.In situ immobilization of palladium nanodots in C-Cbonded 2D conjugated polymers through suzuki polymerization at the liquid-liquid interface.Chem-Eur.J.26,6490-6494(2020).
[0231] 10.Li,C.et al.Two-dimensional conjugated polymer synthesized byinterfacial Suzuki reaction:towards electronic device applications.Angew.Chem.Int.Ed.59,9403-9407(2020).
[0232] 11.Zhang,L.et al.Liquid / liquid interfacial Suzueki polymerizationprepared novel triphenylamine-based conjugated polymer films with excallentelectrochromic properties.ACS Appl.Mater.Interfaces 13,20810-20820(2021).
[0233] 12.Matyjaszewski,K.Advanced materials by atom transfer radicalpolymerization.Adv.Mater.30,1706441(2018).
[0234] 13.Doyle,C.M.et al.Surface mediated synthesis of 2D covalent organicnetworks:1,3,5-tris(4-bromophenyl)benzene on Au(111).Phys.Status Solidi B256,1800349(2019).
[0235] 14.Gutzler,R.et al.Surface mediated synthesis of 2D covalent organicframeworks:1,3,5-tris(4-bromophenyl)benzene on graphite(001),Cu(111),and Ag(110).Chem.Commun.29,4456-4458(2009).
[0236] 15.Bai,B.,Wang,D.&Wan,L.Synthesis of covalent organic framework filmsat interfaces.B.Chem.Soc.Jpn.94,1090-1098(2021).
[0237] 16.Grill,L.&Hecht,S.Covalent on-surface polymerization.Nat.Chem.12,115-130(2020).
[0238] 17.Lee,J.M.&Cooper;A.I.Advances in conjugated microporouspolymers.Chem.Rev.120,2171-2214(2020).
[0239] 18.Chen,H.et al.Benzene ring knitting achieved by ambient-temperaturedehalogenation Via mechanochemical Ullmann-type reductivecoupling.Adv.Mater.33,2008685(2021).
[0240] 19.Gnaim,S.et al.Cobalt-electrocatalytic HAT for functionalization ofunsaturated C-C bonds.Nature 605,687-695(2022).
[0241] 20.Tavakoli,E.et al.In situ bottom-up synthesis of porphyrin-basedcovalent organic frameworks.J.Am.Chem.Soc.141,19560-19564(2019).
[0242] 21.Shi,G.,Jin,S.,Xue,G.&Li,C.A conducting polymer film stronger thanaluminum.Science 267,994-996(1995).
[0243] 22.Wang,X.,She,P.&Zhang,Q.Recent advances on electrochemical methodsin fabricating two-dimensional organic-ligand-containing frameworks.SmartMat2,299-325(2021).
[0244] 23.Zhang,C.,Li,Y.,Li,H.,Zhang,Q.&Lu,J.Overview of electric-field-induced deposition technology in fabricating organic thinfilms.J.Mater.Chem.C 9,374-394(2021).
[0245] 24.Wiebe,A.et al.Electrifying organic synthesis.Angew.Chem.Int.Ed.57,5594-5619(2018).
[0246] 25.Kingston,C.et al.A Survival guide for the“electro-curious”.Acc.Chem.Res.53,72-83(2020).
[0247] 26.Yan,M.,Kawamata,Y.&Baran,P.S.Synthetic organic electrochemicalmethods since 2000:on the verge of a renaissance.Chem.Rev.117,13230-13319(2017).
[0248] 27.Shi,G.,Xue,G.,Li,C.,Jin,S.&Yu,B.Uniaxial oriebted poly(p-phenylene)fibrils and films.Macromolecules 27,3678-3679(1994).
[0249] 28.Abdulkarim,A.et al.A new solution to an old problem:synthesis ofunsubstituted poly(para-phenylene).J.Am.Chem.Soc.138,16208-162ll(2016).
[0250] 29.González-Tejera,M.J.,de la Blanca,E.S.&Carrillo,I.Polyfuranconducting polymers:synthesis,properties,and applications.Synthetic Met.158,165-189(2008).
[0251] 30.Hamby,T.B.,Lalama,M.J.&Sevov,C.S.Controlling Ni redox states bydynamic ligand exchange for electroreductive Csp3-Csp2 coupling.Science 376,410-416(2022).
[0252] 31.Zhang,W.et al.Electrochemically driven cross-electrophile couplingof alkyl halides.Nature 604,292-297(2022).
[0253] 32.Zhang,B.et al.Ni-electrocatalytic Csp3-Csp3 doubly decarboxylativecoupling.Nature 606,313-318(2022).
[0254] 33.Li,Z.et al.Electrochemically enabled,nickel-catalyzeddehydroxylativc cross-coupling of alcohols with arylhalides.J.Am.Chem.Soc.143,3536-3543(2021).
[0255] 34.Jennings,P.W.,Pillsbury,D.G.,Hall,J.L.&Brice,V.T.Carbon-carboubond formation Via organometallic electrochemistry.J.Org.Chem.41,719-722(1976).
[0256] 35.Fox,M.A.,Chandler,D.A.&Lee,C.Electrocatalytic coupling of arylhalides with(1,2-bis(di-2-propylphosphino)beuzene)nickel(0).J.Org.Chem.56,3246-3255(1991).
[0257] 36.Amatore,C.et al.Oxidative addition of aryl halides to transientanionic a-aryl-palladium(0)intermediates-application to palladium-catalyzedreductiVe coupling of aryl halides.Chem-Eur.J.2,957-966(1996).
[0258] 37.Sengmany,S.et al.Preparation of functionalized aryl-andheteroarylpyridazines by nickel-cataIyzed electrochemical cross-couplingreactious.J.Org.Chem.72,563l-5636(2007).
[0259] 38.Studer,A.&Curran,D.P.The eIectron is a catalyst.Nat.Chem.6,765-773(2014).
[0260] 39.Li,C.,Shi,G.,Liang,Y.,Ye,W.&Sha,Z.High-quality poly(p-phenylene)film prepared by electrochemical pol ymerization of benzene at a stainlesssteel electrode.Polymer 38,5023-5026(1997).
[0261] 40.Marucci,A.et al.Resonant raman study of polyparaphenylene-basedcarbons.J.Mater.Res.14,1124-1131(1999).
[0262] 41.Larkin,P.in Infrared and Raman Spectroscopy:Principles andSpectral interpretation Ch.2(Elsevier Press,2011).
[0263] 42.Gin,D.L.,Conticcllo,V.P.&Grubbs,R.H.Stereoregular precursors topoly(p-phenylene)via transition-metal-catalyzed polymerization.2.the effeetsof polymer stereochemistry and acid catalysts on precursor aromatization:acharacterization study.J.Am.Chem.Soc.116,10934-10947(1994).
[0264] 43.Lian,F.,Xu,K.&Zeug,C.The synergism of sequential pairedelectrosynthesis with halogen bonding activation for the cyclization oforganochlorides with olefins.Sci.China Chem.66,540-547(2023).
[0265] 44.Huang,Z.,Qu,L.,Shi,G.,Chen,F.&Hong,X.Electrochemicalpolymerization of naphtalene in the electrolyte of boron trifluoride diethyletherate containing trifluoroacetic acid and polyethylene glycololigomer.J.Electroanal.Chem.556,159-165(2003).
[0266] 45.Johnson,J.P.et al.Comparison of“polynaphthalenes”prepared by twomechanistically distinct routes.J.Am.Chem.Soc.125,14708-14709(2003).
[0267] 46.Fernandez,A.L.,Granda,M.,Bermejo,J.&Menendez,R.CatalyticPolymerization of anthracene oil with aluminium trichloride.Carbon,37,1247-1255(1999).
[0268] 47.Fan,B.,Qu,L.&shi,G.Electrochemical polymerization of anthracene inboron trifluoride diethyl etherate.J.Electroanal.Chem.575,287-292(2005).
[0269] 48.Vorona,M.Y.et al.Developingand comparing 2,6-anthracenederivatives:optical,electrochemical,thermal,and their use in organic thinfilm transistors.Materials 13,1961-1975(2020).
[0270] 49.Lin,K.et al.Electrosynthesis of electroactive and fluorescentpolyphenanthrenes via electropolymerization in BmimPF6.Synthetic Met.209,447-454(2015).
[0271] 50.Nie,G.,Han,X.,Zhang,S.&Wei,Q.Electrosyntheses of high-qualitypolyphenanthrene in the electrolyte of boron trifluoride diethyl ethgratecontaining trifluoroacetic acid.J.Polym.Sci.Pol.Chem.45,3929-3940(2007).
[0272] 51.Li,H.et al.Designingπ-conjugated polypyrene nanoflowers formedwith meso-and microporous nanosheets for high-performanee anode of potassiumion batteries.Chem.Eng.J.430,132704(2022).
[0273] 52.Lu,G.&Shi,G.Electrochemical polymerization of pyrene in theelectrolyte of boron trifluoride diethyl etherate containing trifluoroaceticacid and polyethylene glycol oligomer.J.Electroanal.Chem.586,154-160(2006).
[0274] 53.Lu,G.,Qu,L.&Shi,G.Electroehemical fabrication of neuron-typenetworks based on crystalline oligopyrene nanosheets.Electrochim.Acta 51,340-346(2005).
[0275] 54.Ren,H.et al.Synthesis of a porous aromatic framework for adsorbingorganic Pollutants application.J.Mater.Chem.2l,10348-10353(2011).
Claims
1. A method for producing an aromatic polymer, The following steps are involved: a) providing an anode region and a cathode region; b) providing an aromatic hydrocarbon precursor; c) providing an electrochemical potential between the anode region and the cathode region; d) reacting the aromatic hydrocarbon precursor via the electrochemical potential to form the polymer, wherein the reacting step d) further comprises the step of performing a cathode reaction. 2 . The method according to claim 1 , wherein the cathode reaction further comprises the step of performing a dehalogenation coupling reaction of the aromatic hydrocarbon precursor to form the polymer.
3. The method according to claim 1, wherein the method further comprises the step of providing an anode electrode at the anode region, a cathode electrode at the cathode region, and a solution containing an electrolyte, wherein the anode electrode and the cathode electrode at least partially contact the solution.
4. The method of claim 1, wherein the aromatic polymer is a conjugated polymer; optionally, the aromatic polymer is an unsubstituted conjugated polymer.
5. The method of claim 1, wherein the aromatic polymer is in a form selected from the group consisting of a dimeric form, an oligomeric form, a polymeric form, and combinations thereof.
6. The method of claim 1, wherein the arene precursor is selected from the group consisting of halogenated benzenes, halogenated polycyclic aromatic hydrocarbons, and combinations thereof, and wherein the arene precursor comprises more than one halogen.
7. The method according to claim 6, wherein the halogen is selected from the group consisting of fluorine, chlorine, bromine, iodine and combinations thereof; preferably, the halogen comprises bromine or iodine.
8. The method according to claim 6, wherein the aromatic hydrocarbon precursor is a dihaloaromatic hydrocarbon, optionally, the aromatic hydrocarbon precursor is selected from the group consisting of dihalobenzene, dihalonaphthalene, dihalobiphenyl, dihaloanthracene, dihalophenanthrene, dihalophenalene, dihalopyrene, dihalodiphenylbenzene, dihalotetracene, dihalotriphenylene, dihalo Dihalogenated benzo[c]phenanthrene, dihalogenated benzo[a]anthracene and combinations thereof.
9. The method of claim 8, wherein the arene precursor comprises a first halogen and a second halogen, wherein the second halogen is located at a position on the precursor substantially opposite to the first halogen, and a dehalogenation reaction occurs at the halogen substitution position.
10. The method of claim 1, wherein the aromatic polymer forms a covalent organic framework.
11. The method of claim 10, wherein the aromatic hydrocarbon precursor is a trihaloarene; optionally, wherein the aromatic hydrocarbon precursor is selected from the group consisting of: 1,3,5-trihalobenzene, 1,3,5-tris(4-halophenyl)benzene, and combinations thereof.
12. The method of claim 10, wherein the arene precursor is a tetrahaloarene, optionally wherein the arene precursor comprises 1,3,6,8-tetrahalopyrene.
13. The method according to claim 6, wherein the arene precursor is a dihaloarene or a trihaloarene, and wherein two or three halogens replace corresponding hydrogens at positions of the same arene precursor such that the distance between the two or three halogens is maximized.
14. The method of claim 2, wherein the reacting step d) further comprises the step of allowing the aromatic hydrocarbon precursor to form a free radical intermediate to form the polymer.
15. The method according to claim 1, wherein the aromatic hydrocarbon precursor comprises two or more different aromatic hydrocarbon precursors.
16. The method of claim 1, wherein step b) of providing the aromatic hydrocarbon precursor further comprises the step of adding the aromatic hydrocarbon precursor to the cathode region, wherein the cathode region is separate from the anode region.
17. The method according to claim 3, wherein the reacting step d) further comprises the steps of simultaneously polymerizing the aromatic hydrocarbon precursor to form a polymer and forming the polymer film on the surface of the cathode electrode.
18. The method of claim 3, wherein the electrolyte is selected from the group consisting of hexafluorophosphate, tetrafluoroborate, ammonium bromide, perchlorate, and combinations thereof; optionally, the electrolyte is selected from the group consisting of tetramethylammonium hexafluorophosphate (TMAPF 6 ), tetraethylammonium hexafluorophosphate (TEAPF 6 ), tetrabutylammonium hexafluorophosphate (TBAPF 6 ), potassium hexafluorophosphate (KPF 6 ), tetramethylammonium tetrafluoroborate (TMABF 4 ), tetraethylammonium tetrafluoroborate (TEABF 4 ), tetrabutylammonium tetrafluoroborate (TBABF 4 ), potassium tetrafluoroborate (KBF 4 ), lithium perchlorate (LiClO 4 ) and their combinations.
19. The method of claim 3, wherein the solution further comprises a solvent; optionally, wherein the solvent comprises an anhydrous organic solvent; optionally, the solvent is selected from the group consisting of acetone, acetonitrile, toluene, dichloromethane, chloroform, tetrahydrofuran, dimethylformamide, dimethyl sulfoxide, benzonitrile, and combinations thereof.
20. The method of claim 19, wherein the solvent comprises acetonitrile and toluene; optionally, wherein the ratio of acetonitrile to toluene is from about 8:1 to about 2:1; optionally, the ratio of acetonitrile to toluene is about 4:
1.
21. The method of claim 2, wherein the dehalogenation coupling reaction is performed at a temperature of about 0°C to about 60°C and a constant voltage of about 1.5V to about 3.5V for about 2 hours to about 36 hours.
22. The method of claim 21, wherein the electrolyte comprises tetrabutylammonium hexafluorophosphate at a concentration of about 0.05 mmol / mL to about 1 mmol / mL, and wherein the arene precursor concentration is about 0.001 mmol / mL to about 0.5 mmol / mL.
23. The method according to claim 1, further comprising the step of adding a quenching agent to quench the reaction after the reacting step d); optionally, the quenching agent is selected from the group consisting of: water, salt solution and solvent and combinations thereof.
24. The method of claim 1, further comprising the step of swapping the positive and negative poles of the electrochemical potential after the reacting step d) to quench the reaction.
25. The method according to claim 1, further comprising a step f) of washing the polymer with a washing agent selected from the group consisting of water, ethanol, methanol, n-hexane, 2-dichlorobenzene, dichloromethane, 1,2-dichloroethane, tetrahydrofuran, heptane, ethyl acetate, toluene, acetonitrile and combinations thereof after the reacting step d).
26. The method of claim 1, wherein the method comprises a step of drying the polymer after the reacting step d) at a drying temperature of about room temperature to about 250°C, or about room temperature to about 70°C, or about 70°C to about 150°C, or about 80°C to about 100°C; optionally, wherein the drying step is performed under vacuum for a period of about 1 hour to about 12 hours, or about 1 hour to about 6 hours, or about 1 hour to about 4 hours, or about 6 hours to about 12 hours, or about 8 hours to about 12 hours.
27. The method of claim 3, wherein the anode electrode comprises a conductive substrate; preferably wherein the substrate comprises an inert conductive electrode formed from the group consisting of platinum, titanium, alloys thereof, and combinations thereof.
28. The method of claim 3, wherein the cathode electrode comprises a conductive substrate formed from a group consisting of silicon, nickel, gold, platinum, stainless steel, alloys thereof, and combinations thereof.
29. A polymer produced according to the method of claim 1.
